Neutrophils, eosinophils, and mast cells in the intestinal wall of dogs naturally infected with Leishmania infantum - da Silva, Diogo Tiago [UNESP]; Alves, Maria Luana [UNESP]; Spada, Júlio Cesar Pereira [UNESP]; da Silveira, Rita de Cássia Viveiros [UNESP]; Oliveira, Trícia Maria Ferreira de Sousa; Starke-Buzetti, Wilma Aparecida [UNESP] (FapUNIFESP (SciELO), 2018)
Visceral leishmaniasis (VL) is a disease caused by the protozoa Leishmania infantum and can cause an inflammatory reaction in the gastrointestinal tract, however the role of granulocytic cells (neutrophils, eosinophils, and mast cells) in the intestine of dogs infected is not fully understood. We performed a quantitative analysis these cells in the intestinal wall of dogs with canine visceral leishmaniasis (CVL). Twenty dogs were assigned to one of three groups: group 1 (G1, n=8), dogs with CVL and L. infantum amastigotes in the intestine; group 2 (G2, n=9), dogs with CVL but without intestinal amastigotes; and group 3 (G3, n=3), uninfected dogs (control group). Granulocytic cells were counted in the crypt-villus unit (mucosa), submucosa, and muscle layer of the intestinal mucosa. Cell counts were higher in the intestinal wall of dogs from G2 followed by G1 and G3 (p≤0.05). In G1, there was a low inverse correlation between parasite burden of the small intestine and granulocyte counts (r=-0.1, p≤0.01). However, in G2 dogs, mast cell and eosinophil numbers showed positive correlation (r=0.85, p≤0.01). The granulocytic cell hyperplasia observed in the intestine of L. infantum-infected dogs suggests that these cells may be involved in the cell-mediated immune response for parasite elimination.
Neutrófilos, eosinófilos e mastócitos na parede intestinal de cães naturalmente infectados com Leishmania infantum
Keywords: Canine visceral leishmaniasis; Granulocytes; Intestinal tract